2019
DOI: 10.1111/pce.13677
|View full text |Cite
|
Sign up to set email alerts
|

Elevated [CO2] alleviates the impacts of water deficit on xylem anatomy and hydraulic properties of maize stems

Abstract: Plants can modify xylem anatomy and hydraulic properties to adjust to water status. Elevated [CO2] can increase plant water potential via reduced stomatal conductance and water loss. This raises the question of whether elevated [CO2], which thus improves plant water status, will reduce the impacts of soil water deficit on xylem anatomy and hydraulic properties of plants. To analyse the impacts of water and [CO2] on maize stem xylem anatomy and hydraulic properties, we exposed potted maize plants to varying [CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 85 publications
(117 reference statements)
0
17
0
Order By: Relevance
“…The solid pith was consisted of parenchyma cells. Vessel roundness with diameter, stem cross-sectional of area stem, specific hydraulic conductivity, and embolism decreased under moisture stress condition but these impacts of stress were reduced at higher level of atmospheric CO2 [16].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The solid pith was consisted of parenchyma cells. Vessel roundness with diameter, stem cross-sectional of area stem, specific hydraulic conductivity, and embolism decreased under moisture stress condition but these impacts of stress were reduced at higher level of atmospheric CO2 [16].…”
Section: Discussionmentioning
confidence: 90%
“…Size and number of constituents of secondary xylem also affected by elevated CO2. In terrestrial vegetation long-distance, less resistance water transport path, xylem allows quick and extensive movement of water from roots to foliage and is required to maintain gas exchange in leaves under dry environment [16]. Therfore elevated CO2 may have positive response to alleviation of tress by modifying or altering the xylem physiology.…”
Section: Original Research Articlementioning
confidence: 99%
“…A contrasting response was seen in the two grasses to elevated CO 2 and water stress, the difference in the species response was due to the stomatal characteristics as evident by the changes in transpiration rate and osmotic adjustment. Water status adjustment by modification of xylem anatomy and hyrdolyic properties is a mechanism found in many plants, its relationship with the observed effect of elevated CO 2 to increase plant water potential via reduced stomatal conductance and water loss was studied by Liu et al (2020). One the known adaptation to water stress by plants is to maintain high water potential and turgor pressure under water deficient conditions.…”
Section: Water Relations Transpiration and Stomatal Conductancementioning
confidence: 99%
“…8). Several studies showed that WD decreased the diameter of xylem vessels, in tomato pedicel (Rancic et al, 2008), in grape (Lovisolo and Schubert, 1998) and in maize (Abdel-Rahim et al, 1998 ;Liu et al, 2019). On poplar tree, Arend and Fromm (2007) showed that WD provoked a decrease in vessel size, but also an increase in the number of newly formed vessel cells.…”
mentioning
confidence: 99%